2016
DOI: 10.1021/acs.organomet.6b00691
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ferrocene on Carbon Nanotubes, Graphene, and Activated Carbon

Abstract: Ferrocene could be adsorbed on activated carbon, carbon nanotube surfaces, graphite, and graphene in the absence of a solvent at room temperature in spite of its high melting point (174 °C). In each case only monolayers formed via self-adsorption and the transition to surplus polycrystalline material was abrupt, with no multiple layers occurring. Variable-temperature multinuclear solid-state NMR spectroscopy was applied to study the mobilities of the surface-adsorbed ferrocene molecules. It has been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 76 publications
(238 reference statements)
3
34
0
Order By: Relevance
“…Indeed,t he 31 Pw ideline and MAS spectra ( Figure 9) of 4a show that the CSA is only reduced, but not averaged out entirely.T he size of the molecule andt he long alkyl chains are not expected to slow the motion of an adsorbed species because it has been demonstrated earlier that paraffin, cyclododecane, or metallocenes with cycloalkyl substituents are highly mobile on silica and other surfaces. [13][14][15][16] Upon adsorption of 4 to form 4a all CSA parameters and the span of the signal are changed significantly,t he latter by nearly 100 ppm (Table2). Therefore, it can be concluded that both P=Og roups in the molecule are interacting equallyw ith the surfaceo fs ilica, but they actually do impedee ach other's mobility to some extent.…”
Section: C and 31 Ps Olid-state Nmr Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed,t he 31 Pw ideline and MAS spectra ( Figure 9) of 4a show that the CSA is only reduced, but not averaged out entirely.T he size of the molecule andt he long alkyl chains are not expected to slow the motion of an adsorbed species because it has been demonstrated earlier that paraffin, cyclododecane, or metallocenes with cycloalkyl substituents are highly mobile on silica and other surfaces. [13][14][15][16] Upon adsorption of 4 to form 4a all CSA parameters and the span of the signal are changed significantly,t he latter by nearly 100 ppm (Table2). Therefore, it can be concluded that both P=Og roups in the molecule are interacting equallyw ith the surfaceo fs ilica, but they actually do impedee ach other's mobility to some extent.…”
Section: C and 31 Ps Olid-state Nmr Spectroscopymentioning
confidence: 99%
“…Encouraged by the meaningful results obtained with 1 Hw ideline NMR of adsorbed metallocenes [12][13][14][15][16] andm obile species in polymers [50] we probed 4 and 4a with this technique. The proton wideline spectrum of 4 shows as ignal that is broadened by large homonuclear dipolar interactions [17][18][19] and spans from about À110ppm to + 120 ppm, with ah alfwidth of ca.…”
Section: C and 31 Ps Olid-state Nmr Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations